2020
DOI: 10.1038/s41598-020-62261-y
|View full text |Cite
|
Sign up to set email alerts
|

Rosuvastatin alters the genetic composition of the human gut microbiome

Abstract: The gut microbiome contributes to the variation of blood lipid levels, and secondary bile acids are associated with the effect of statins. Yet, our knowledge of how statins, one of our most common drug groups, affect the human microbiome is scarce. We aimed to characterize the effect of rosuvastatin on gut microbiome composition and inferred genetic content in stool samples from a randomized controlled trial (n = 66). No taxa were significantly altered by rosuvastatin during the study. However, rosuvastatin-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 40 publications
2
23
0
Order By: Relevance
“…Participants with a poor treatment response to rosuvastatin also showed a significant increase in TMAO values compared to other participants treated with placebo [ 89 ]. Another study evaluated gut microbial communities in hypercholesterolemic patients treated with atorvastatin.…”
Section: Cholesterol-lowering Agentsmentioning
confidence: 99%
“…Participants with a poor treatment response to rosuvastatin also showed a significant increase in TMAO values compared to other participants treated with placebo [ 89 ]. Another study evaluated gut microbial communities in hypercholesterolemic patients treated with atorvastatin.…”
Section: Cholesterol-lowering Agentsmentioning
confidence: 99%
“…Previous studies found that drugs like proton pump inhibitors (PPIs) and statins could affect the gut microbiota compositions profoundly [30,31], but there was scarce information about the effect of drugs on the gut microbiota metabolites. Recently, a small cohort study found that rosuvastatin therapy not only affected the genetic compositions of gut microbiota, but also may affect the gut microbiota metabolites [13]. Patients in rosuvastatin therapy group had higher betaine and γBB levels than placebo group, and the TMAO and carnitine levels in rosuvastatin therapy group also tended to decrease and increase separately, although the differences were not signi cant [13].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a small cohort study found that rosuvastatin therapy not only affected the genetic compositions of gut microbiota, but also may affect the gut microbiota metabolites [13]. Patients in rosuvastatin therapy group had higher betaine and γBB levels than placebo group, and the TMAO and carnitine levels in rosuvastatin therapy group also tended to decrease and increase separately, although the differences were not signi cant [13]. In this study we found that, rosuvastatin therapy could decrease TMAO, but increase carnitine, betaine and γBB levels signi cantly while it lowering the blood lipids levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For host‐targeted drugs, increasing evidence suggests that they are associated with shifts in gut microbiome composition. Known examples span a broad range of therapeutic classes and include the antidiabetic metformin, proton‐pump inhibitors, antipsychotics, non‐steroidal anti‐inflammatory drugs, paracetamol, opioids, selective serotonin reuptake inhibitors, laxatives, and statins (Le Bastard et al , 2018; Jackson et al , 2018; Kummen et al , 2020; MetaCardis Consortium et al , 2020). These shifts are not necessarily unfavorable for the host.…”
Section: Introductionmentioning
confidence: 99%